An evaluation of co-management practices: A case of a South African platinum mine management and the local community - Matsimela, Tebogo Mapipi (Rhodes University, Faculty of Commerce, Rhodes Business School, 2021)
A vast body of literature reveals the paradigm shift of South Africa's economy from an agricultural community to an industrial economy. Elbra (2013) illustrated that South African mining host communities viewed that mineral endowments have become a "resource curse" instead of a driver of local economic development for the benefit of the community. To understand the mining and community conflict and their subsequent complexities, the Marikana massacre in August 2012 must be revisited (Bell, 2016). The problems may be broadly summarised as a lack of stakeholder engagement and inclusivity. Studies involving stakeholder management and co-management focused on the identification of stakeholders and their management. The research evaluated the co-management practices between mine management and a local community. It considered the challenges that emanated from the co-management practices. The primary focus of this research has been to evaluate the co-management features between the mine management and the local community and to identify the challenges associated with co-management from a mine management perspective. Furthermore, the research attempted to find effective co-management practices between the mine management and the local community which may be used to improve the partnership. Armitage, Berkes and Doubleplay (2007) recognised that in facilitating effective co-management, the commitment towards fulfilling good governance and accountability was paramount in ensuring that the rights and obligations of both private and public actors were achieved. However, Ran and Qi (2018) acknowledged that such partnerships were not immune to challenges because the poor implementation of co-management features like power-sharing could collapse a co-management partnership. This study aimed to evaluate the current co-management practices from the mine management's perspective. A literature search revealed the range of co-management features that explained the different use of practices. The features included co-management and power sharing, co-management and institution building, co-management and trust and social capital, co-management as a process, co-management and problem solving, and co-management and governance. The study evaluated the co-management features between the mine management and the local community, identified the current challenges associated with co-management from a mine management perspective and attempted to make recommendations on effective co-management practices between the mine management and a local community. A qualitative case study method was employed. This method allowed the researcher to evaluate multifaceted matters which may have been investigated in the past but not inconsiderable detail (Baxter and Jack, 2008). Data was sampled using purposive sampling. This was because the population sample was chosen according to their roles and responsibilities and their involvement in the co-management between the mine management and the local community. Data was collected through semi-structured interviews and document analyses. The findings of the research were derived from a range of company documents. Thematic analysis was employed to understand the practices of co-management which underpinned the co-management partnership between the mine management and the local community. It was found that there was a positive relationship between the literature study and the response from the mine management. The shared responsibilities emerged out of a dialogue characterised by deliberation and negotiations between the mine management and the stakeholders. Berkes (2009), asserted that co-management bore a resemblance to the process of the sharing of ideas of how responsibilities could be better shared and that it emanated from a process of deliberation and negotiation. Furthermore, if the evolution of the co-management partnership was not managed carefully, it could pose a risk to the partnership itself. It was acknowledged by the research respondents that there were complications involved in having the community as a shareholder in the mine, but equally, the community showed an appreciation of being involved in building a sustainable mine. The model of sustainable partnership emphasised that any viable partnership should adopt this model to achieve a sustainable performance (Thomson and Boutilier, 2011). This research showed that the co-management practices between the mine management and the local community concurred with the findings of Zvarivadza (2018). Trust and transparency between mine management and the community could go a long way in ensuring that the mine fulfilled its legal responsibilities in the local community where the mine is located.
Keywords: Mines and mineral resource -- Management -- South Africa; Mines and mineral resource -- Management -- Social aspects; Mines and mineral resource -- Management -- Moral and ethical aspects; Platinum mines and mining -- Management -- South Africa -- Case studies; Corporate governance -- South Africa -- Case studies